2017
DOI: 10.1177/0748233717715187
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary effects of temporal exposure to cigarette smoke

Abstract: This study aimed to evaluate the extrapulmonary effects of exposure to cigarette smoke (CS) through the analysis of blood components and histopathological examinations of the trachea and diaphragm muscle (DM) in C57BL/6 mice. Thirty-six animals were exposed to six cigarettes per day for 5 days. The mice were divided into a control group (CG) and groups exposed to CS for 1 (CS1D), 2 (CS2D), 3 (CS3D), 4 (CS4D), and 5 (CS5D) days. The trachea, DM, and blood were collected for morphometric and biochemical analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Cigarette smoking is a crucial risk factor for cancers, respiratory, and cardiovascular diseases (Martins et al, 2017). Cigarette smoking is also an established risk factor for some oral diseases, such as periodontal disease, oral leukoplakia, and oral cancer (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoking is a crucial risk factor for cancers, respiratory, and cardiovascular diseases (Martins et al, 2017). Cigarette smoking is also an established risk factor for some oral diseases, such as periodontal disease, oral leukoplakia, and oral cancer (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Augmented levels of AST and gamma-GT were also observed in the untreated smoke-exposed group in our studies. Other research showed significant increase in biochemical parameters related to liver function, as serum levels of alanine aminotransferase (ALT), AST and total cholesterol were significantly higher in mice that were short-term exposed to cigarette smoke [39]. Moreover smokers with elevated blood pressure and serum gamma-GT levels are at higher risk of developing chronic kidney disease [49].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that levels of aspartate aminotransferase (AST), gamma glutamyl transferase (gamma-GT), glucose and cholesterol have been associated with cases of patients with exacerbated COPD [37][38][39][40]. Due to this we also investigated these biochemical parameters in the blood.…”
Section: Biochemical Blood Assaysmentioning
confidence: 99%
“…After short-term exposure to CS for 5 days, the trachea and diaphragm of mice were infiltrated by inflammatory cells (Martins et al, 2017). Long-term CS exposure increases the risks of chronic obstructive pulmonary disease, lung cancer, and premature death (Nyunoya et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…CS inhalation has been reported to activate lung epithelial cell inflammation, cause DNA damage, and induce cell death ( Nyunoya et al, 2014 ). After short-term exposure to CS for 5 days, the trachea and diaphragm of mice were infiltrated by inflammatory cells ( Martins et al, 2017 ). Long-term CS exposure increases the risks of chronic obstructive pulmonary disease, lung cancer, and premature death ( Nyunoya et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%